Asuhan Kebidanan pada Ibu Primi Gravida Usia Remaja di TM II Sebagai Kehamilan Risiko Tinggi: Laporan kasus - Rina Cahya Nurani; Nuryani .; Suparji . (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Introduction: Pregnancy in adolescence (<20 years) is a high-risk pregnancy due to biological and psychosocial immaturity that can increase the risk of maternal and perinatal complications, such as anemia, preeclampsia, preterm labor, and low birth weight babies. This condition requires early detection and comprehensive midwifery care to optimize maternal and fetal health. The purpose of this study is to describe the implementation of comprehensive midwifery care for adolescent primigravida pregnant women in the second trimester with high-risk pregnancies. Methods: Using a design (case report) on Mrs. "N" aged 15 years G1P0A0 gestational age 23–24 weeks with a high-risk pregnancy. The assessment was analyzed using midwifery care management according to Varney, then documented using the SOAP method (Subjective, Objective, Assessment, and Management).  Results and Discussion: The mother had a height of ≤145 cm, BMI 23.3 kg/m², MUAC 24.8 cm, and MAP 93.3 mmHg. Her weight increased to 52 kg. Fetal growth was in accordance with gestational age, and no danger signs or complications were found in the mother and fetus. Conclusions: There was an increase in the mother's weight after this care, vital signs and DJJ remained normal, and no danger signs or complications were found.